Cognition, Emotion and Behaviour: Addressing the Relationship Between Executive Functions and Decision-Making - Gonzalez Aguilar, Maria Josefina (2021)
Executive functions are a complex and heterogeneous group of concepts that refer to a set of diverse cognitive abilitiessuch as working memory, cognitive flexibility, planification, reasoning, problem-solving and inhibition. Moreover, decision-making maybe described as a pattern that a person uses when he or she is facing a situation where they must lean towards an option: people tendto choose one or another option considering the risks and benefits these options offer. There is evidence supporting that executivefunctions are associated with the way people make their decisions. The main aim of the present study is to review and update theseconcepts reporting evidence from the literature on the association between the cognitive, emotional, and behavioral aspects of decisionmaking.